Healing Through Expressive Arts: A Path to Success for Children with ADD and ASD - Anderson, Stephany (My University, 2018)
This paper explores the relief expressive art therapy offers children with Attention Deficit Disorder (ADD) and Autism Spectrum Disorder (ASD). The paper defines expressive art therapy, it's evolution, and how expressive art therapy aids communication, builds social skills and creates a supportive community for children with these diagnoses. In addressing children's emotional needs expressive art therapy can have an impact on the child's behavior and ability to learn. Current research and case studies are presented that support expressive art therapy's efficacy with children with ADD and ASD.
Keywords: Art Therapy; Autism Spectrum Disorder; Attention Deficit Disorder